Thermodynamic Solar Power in Africa. SOFRETES or the French Solar and Thermal Energy Company (1973-1983) - (:unkn) unknown (My University, 2017)
The paper deals with the history of the Sofretes, a small French private-public mixed economic company specialized in solar-powered water pumping system, and created by the French engineer Jean-Pierre Girardier in 1973. World leader during ten years, this company finished its life in the entire property of the CEA (French research agency in Atomic Energy). The article put the story in the long term of “solar power engineering” and its specific association with the African continent. We examine the first period of 1860-1920, and after the second, at the beginning of the sixties, with the initiatives of the university physic professors Henri Masson, founder of the Dakar Faculty of Science, and Abdou Moumouni Dioffo, from Niger, the most important African solar researcher of the time.
Keywords: African Research